Air ambulance flights in northern Norway 2002- 2008. Increased number of secondary fixed wing (FW) operations and more use of rotor wing (RW) transports - Norum, Jan; Elsbak, Trond M (International Journal of Emergency Medicine, 2011)
Air ambulance service in Norway has been upgraded during the last years. European regulations concerning pilots’ working time and new treatment guidelines/strategies have called for more resources. The objective was to describe and analyse the two supplementary air ambulance [fixed wing (FW) and rotor wing (RW)] alternatives’ activity during the study period (2002-2008). Furthermore we aimed to compare our findings with reports from other north European regions. This is a retrospective analysis. The air ambulance fleet’s activity according to the electronic patient record database of “Luftambulansetjenesten ANS” (LABAS) was analysed. The subject was the fleet’s operations in northern Norway, logistics, and patients handled. Type of flight, distances, frequency, and patients served were the main outcome measures. A significant increase (45%) in the use of RW and a shift in FW operations (less primary and more secondary) were revealed. The shift in FW operations reflected the centralisation of several health care services [i.e. percutaneous cardiac intervention (PCI), trauma, and cancer surgery] during the study period. Cardiovascular disease (CVD) and injuries were the main diagnoses and constituted half of all operations. CVD was the most common cause of FW operations and injuries of the RW ones. The number of air ambulance operations was 16 per 1,000 inhabitants. This was more frequent than in other north European regions. The use of air ambulances and especially RW was significantly increased during the study period. The change in secondary FW operations reflected centralisation of medical care. When health care services are centralised, air ambulance services must be adjusted to the new settings.